PTU-110 Endoscopy insourcing is a safe way to deliver additional capacity. (8th June 2018) - Khan, Iqbal; Mahachi, Lorraine; Drew, Kaye
Abstract : Introduction: There is an unprecedented burden on UK endoscopy units and the current demand for endoscopic procedures is disproportionate to the capacity to deliver endoscopy activity. Units are addressing this in various ways including insourcing of staff to carry out endoscopy work. This is especially useful at weekends when the Unit would often be inactive. Medinet is a well-established provider of endoscopy insourcing across the UK. Their endoscopists hold substantive posts within the NHS and nurses are highly experienced specialised endoscopy nurses. Methods: Medinet's database was interrogated for the total numbers of endoscopic procedures carried out over a 12 month period (1 st Jan – 31 Dec 2017). This endoscopy work was carried out in NHS hospitals all over the UK. Medinet has a robust governance process (which includes regular governance meetings) where all complaints and adverse incidents are discussed and dealt with in a timely fashion. Such incidents were reviewed over this 12 month period. Results: Over the 12 months 25 347 endoscopic procedures were carried out: 12 137 colonoscopies, 10 564 gastroscopies and 2646 flexible sigmoidoscopies. Over this period only 17 complaints were received (0.07%). Most of these related to patient perception and general operational issues. At governance meetings it was agreed that no or minimal harm was done. Over the same period there were a total of 28 adverse incidents (0.11%). These included one perforation, procedure related bleeds, a missed early malignant lesion, incorrect labelling of specimens, drug documentation errors and problems with the reporting system. There were no deaths related to the procedures but there was one reversal of sedation, which was deemed a never event. Conclusion: Insourcing of endoscopy services has grown dramatically over the last few years and gives UK endoscopy units a viable alternative to ensure they keep up with the tremendous pressures to maintain capacity and timeliness in a time of growing demand, limited resources and increasing quality standards. This data confirms that with the correct personnel and governance in place, insourcing is extremely safe with low level of complaints and adverse incidents.